Serum Orexin-A, Oestrogen, Leptin, RBP-4 Levels, Body Composition and Cardiovascular Risk Parameters in Migraine: A Case-Control Study - Yıldıran, Hilal; Gezmen Karadağ, Makbule; Ertaş-Öztürk, Yasemin; Ayyıldız, Feride; Yücalan-Girgin, Özgül Bike (Progress in Nutrition, 2020)
Aim: Tension-type headache and migraine are common health disorders recently associated with increased risk of obesity and chronic diseases. In the present study, comparison of anthropometric measurements, body composition, and cardiovascular parameters as well as serum orexin-A, oestrogen, leptin and retinol binding protein-4 levels as whether being a potential clinical markers in females with migraine and tension-type headache (TTH) with healthy controls was aimed.Methods: This case-control study conducted on female individuals with migraine without aura (n:30), TTH (n:29) and a control group (n:27) in Ankara between 2016-2017. Anthropometric measurements and body compositions were taken and blood pressures, serum glucose, insulin, lipid profile, orexin-A, leptin, oestrogen, retinol binding protein-4 and Homeostatic Model Assessment-Insulin Resistance levels were measured. The participants in the migraine group were asked about frequency of attacks, attack duration and pain severity.Results: In the migraine group, higher serum cholesterol levels than the tension-type headache group and higher systolic and diastolic blood pressure levels than the control group were observed. A significant increase in attack duration was related with the increased blood pressures in migraine patients. There was no difference found between the groups in terms of anthropometric measurements, serum orexin-A, oestrogen, leptin and retinol binding protein-4 levels.Conclusion: Monitoring the migraine patients for cardiovascular risk is essential. Further studies should be conducted to evaluate differences between headache groups in terms of peptide levels.